2015
DOI: 10.1007/s11904-015-0273-9
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Statins in the Setting of HIV Infection

Abstract: HIV-infected individuals are at an increased risk of cardiovascular disease (CVD) and other HIV-related co-morbidities. This is due in part to dyslipidemia associated with antiretroviral therapy and increased inflammation and immune activation from chronic HIV infection. Statins not only have potent lipid-lowering properties but are also anti-inflammatory and immunomodulators. Studies suggest that statin therapy in the HIV-infected population may decrease the risk of CVD and other non-AIDS-defining co-morbidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 76 publications
0
28
0
1
Order By: Relevance
“…Indeed, most of the statins interfere with metabolism of anti-retroviral drugs due to the fact that they are metabolized via the cytochrome P450 3A4 isoform, inducing increased toxicity (13). These safety warnings have limited statin therapy in HIV-infected individuals receiving simultaneous antiretroviral therapy (35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, most of the statins interfere with metabolism of anti-retroviral drugs due to the fact that they are metabolized via the cytochrome P450 3A4 isoform, inducing increased toxicity (13). These safety warnings have limited statin therapy in HIV-infected individuals receiving simultaneous antiretroviral therapy (35).…”
Section: Discussionmentioning
confidence: 99%
“…These safety warnings have limited statin therapy in HIV-infected individuals receiving simultaneous antiretroviral therapy (35). Since pravastatin is a cytochrome P450 independent and water- The mechanism underlying the interactions between pravastatin and anti-retroviral drugs may be due to a competition at the cytochrome level that transports protein P-glycoprotein and may also be caused by genetic polymorphism (13). However, in HIV-infected patients on statin therapy, it has been recommended that plasma concentrations of protease inhibitors be evaluated to avoid drug-drug interaction (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antiretroviral treatment is known alter lipid levels, and also interact with statin therapy 6 . This means that statins can have different lipid-lowering potencies and immunomodulatory effects in HIVinfected individuals compared to uninfected individuals 7 . Only a single recent small study assessed the effect of atorvastatin on liver fat in a group of HIV-infected individuals with NAFLD and showed an improvement in hepatic steatosis with statin therapy 8 .…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Some clinical studies have demonstrated anti-inflammatory and immunomodulatory properties of statins in HIV-infected people too, but data are limited and not always concordant. 12,13 Moreover, data are still lacking about the statin effect on the coagulation markers in HIV-infected patients.…”
Section: Introductionmentioning
confidence: 99%